ANALISIS KUALITAS PELAYANAN CUSTOMER SERVICE TERHADAP KEPUASAN NASABAH PADA BANK BRI KCP PANAM PEKANBARU - Hardiningsih Hardiningsih; Adriyanti Agustina Putri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to analyze and describe the quality of service to customer satisfaction at the BRI bank KCP Panam Pekanbaru. The type of data in this study is secondary data. Data collection methods in this research are field studies and literature studies. The research method used is descriptive qualitative. The results of this study are, first: Customer service plays an important role in the best service to customers. Therefore, Bank BRI KCP Panam Pekanbaru prioritizes appearance standards for its customer service, such as dressing politely, neatly and cleanly. Second: Customer service as a communicator is in charge of providing all information about bank products or services to customers, accommodating customer complaints and objections. Bank BRI KCP Panam Pekanbaru prioritizes customer service to carry out tasks according to standard operating procedures. For this reason, the customer service of Bank BRI KCP Panam Pekanbaru must be smiling, fluent, friendly, calm and patient in serving every customer.